Expression and Purification of Serine/Arginine-Rich Splicing Factor 1 from Escherichia coli Expression System - ZHANG Minmin; ZHANG Yunlong; CHEN Ting; LU Changrui (东华大学学报（英文版）, 2022)
Q71; Serine/arginine-rich splicing factor 1 (SRSF1), as a prototype member of the highly conserved serine/arginine family of RNA binding proteins, plays an important role in mRNA alternative splicing, stabilization, nuclear export, and translation. Here, the expression system was established to purify full-length human SRSF1 from Escherichia coli ( E. coli). The SRSF1 coding sequence was amplified by polymerase chain reaction (PCR) and inserted into the pET-28a-ppSUMO vector with His-tag to construct a recombinant plasmid His-SUMO-SRSF1. Then the plasmid was transformed into BL21 (DE3) competent cells for expression. After purification by affinity chromatography and cleavage of His-SUMO moiety, a highly purified SRSF1 with a molecular weight of around 28 kg/mol was obtained. The protein was analyzed by sizing chromatography and it was found that SRSF1 would form a polymer structure in the solution. According to Expasy bioinformatics analysis, SRSF1 is extremely unstable. Purification of full-length SRSF1 protein provides an opportunity to study mRNA splicing in vitro.